1994
DOI: 10.1016/0014-5793(94)80582-2
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite releases copper from caeruloplasmin: implications for atherosclerosis

Abstract: Peroxynitrite may be formed in the vasculature by the reaction of superoxide with nitric oxide. When the blue copper-containing protein, caeruloplasmin, is incubated with peroxynitrite, copper is released, and ferroxidase activity and the blue colouration are lost. When plasma from normal subjects is incubated with peroxynitrite, the oxidant reacts with numerous plasma constituents but is still able to release copper from caeruloplasmin. As the ferroxidase activity of caeruloplasmin is lost in plasma in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
1
1

Year Published

1995
1995
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(62 citation statements)
references
References 22 publications
0
60
1
1
Order By: Relevance
“…As expected, Chelex-100 removed either copper or iron ions that had been added to Ham's F-10 medium and prevented them from catalysing LDL oxidation. These observations are supported by the work of Smith et al [17] and Swain and Gutteridge [18], who showed that gruel from atherosclerotic lesions contained significant levels of catalytically active copper and iron ions that were able to catalyse the oxidation of rat liver microsomes or linoleic acid micelles.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…As expected, Chelex-100 removed either copper or iron ions that had been added to Ham's F-10 medium and prevented them from catalysing LDL oxidation. These observations are supported by the work of Smith et al [17] and Swain and Gutteridge [18], who showed that gruel from atherosclerotic lesions contained significant levels of catalytically active copper and iron ions that were able to catalyse the oxidation of rat liver microsomes or linoleic acid micelles.…”
Section: Discussionmentioning
confidence: 57%
“…confirmed by Swain and Gutteridge [18], who also showed that lesions can contain ferrioxidase I activity, due to caeruloplasmin, and immunologically-detectable caeruloplasmin. Ferroxidase 3 activity, due to xanthine oxidase, was also present in some lesions.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The insertion of seeding 275 peroxides into the LDL particle could proceed through a reaction dependent upon 15-1ipoxygenase [40,41]. The relevance of copper dependent oxidation to atherosclerosis is also debatable but the recent finding of redox active transition metals in human atherosclerotic lesions and the peroxynitrite dependent release of copper from caeruloplasmin, the major extracellular copper containing protein, provide the evidence for its presence in lesions and a possible mechanism for its release [27,42]. However, it is important to note that tocopherol mediated peroxidation was only detectable in samples of LDL with low lipid hydroperoxide content and a high intrinsic resistance to oxidation (Fig.…”
Section: Discussionmentioning
confidence: 99%